Pengukuran Persepsi Peserta Didik terhadap Penggunaan Aplikasi Prezi dalam Pembelajaran IPA - Ellyna Hafizah*; Siti Nurhaliza; Yudha Irhasyuarna (JIPI (Jurnal IPA dan Pembelajaran IPA), 2022)
he less qualified presentation of content on a learning media will affect students’ perceptions.The aim of this study is to obtain students’ perceptions toward Prezi using in a science learning. This study uses a descriptive quantitative method. The data were collected by perception questionnaire sheets to 20 students in class VIII-E of SMPN 9 Banjarmasin. The results showed that the students’ perceptions are categorized as positive, as follows 40% of them have the perceived ease of use, 50% of them have the perceived usefulness, 60% of them have the attitude of use and 45% of them have intention of use. Thus, students have believed that Prezi is easy and useful for the science learning as well as accepted if it re-apply to other topics. The results canbe considered to test a hypothesis toward the effect of each perception’s aspect in the future study